Pemberian Informasi Terhadap Tingkat Kecemasan pada Anak Sekolah Dasar Sebelum Khitan - Dini Qurrata Ayuni; Waldi Rahman; Mona Yolanda; Septa Nelli; Helman Pelani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Circumcision or minor surgery, has long been known in human culture. Circumcision is a simple surgical procedure in which the skin of the penis is cut to remove the folds of skin that normally cover the head of the penis. Circumcision is a surgical procedure that removes the foreskin of the penis for medical purposes. Providing information on the level of anxiety in elementary school children before circumcision, a community service activity, aims to reduce students' anxiety in dealing with circumcision or circumcision. This community service was carried out at SDN 27 VII Koto Sungai Sarik, Padang Pariaman Regency. The evaluation of the activities was analyzed using pre and posttests regarding the level of anxiety of students in facing circumcision or circumcision. before being given information about circumcision or circumcision, after being given information about circumcision, most of the students 66.7% were no longer worried about facing circumcision. It can be concluded that providing information about circumcision or circumcision is very necessary for students as an effort to reduce anxiety in dealing with circumcision or circumcision